Factors Related to Successful Breastfeeding at King Narai Hospital, Lopburi Province - Owatanapanich, Somchai; Sommang, Kotchakorn; Sukprasong, Panida (Journal of Health Science of Thailand, 2017)
The purpose of this study was to identify factors related to successful breastfeeding, infant health status. The study was cross sectional descriptive study. Data collection was done in 210 couples of mothers and babies born at King Narai Hospital in 2012. Analytical statistics used in this study were Chi-Square, Fisher’s exact, Spearman rank difference method and described in odds ratio and statistical significant p<0.05. The study showed 43.3% mothers could achieve 6 months exclusive breastfeeding (6-mo EBF) and 29.1% mothers could continue breastfeeding over 12 months. Factors that significantly associated with 6-mo EBF were education, occupation, place of antenatal care, order of babies, breastfeeding attitude, maternal experience, labour/postpartum care, breastfeeding support clinic, home visit in community, family, giving 6-12 months successful breastfeeding certificates, breastfeeding promoting team, Saiyairak community network. A significant defensive factor was duration of maternity leave. The infants in the group of more than 12 months breastfeeding had all health status better than in the group of below 12 months breastfeeding. The health status were weight for age, height for age, weight for height, development, allergy and sickness. This study found that maternal personal factors, health services factors, family support, provincial breastfeeding policy with honor recognition will haveimpact in breastfeeding promotion and increase exclusive breastfeeding rate in Lopburi province. The authors propose King Narai Breastfeeding Model to develop social movement in order to sustain breastfeeding practice society.